PELAKSANAAN PROGRAM PENINGKATAN PARTISIPASI POLITIK PEMILIH PEMULA OLEH KPU KOTA JAMBI TAHUN 2024 - Syaputra, Muchtar Imam; ,, Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to describe the program implementation by the Electoral Commission (KPU) Jambi City to increase political participation for novice voters in 2024. Novice voters are a strategic group in democracy, but tend to have low participation rates due to a lack of political experience and political knowledge. Jambi City was recorded as the region with the lowest participation in the 2024 Regional Head Elections in Jambi Province, despite having a significant number of novice voters. This study employed a descriptive qualitative approach, utilizing data collection techniques that included interviews, documentation, and literature reviews. The results showed that the KPU Jambi City implemented a strategy through three main stages: formulation and long-term targets, selection of actions such as direct outreach to schools and campuses, and the use of social media, as well as resource allocation, including the involvement of Adhoc agency and technical training. Inhibiting factors included a lack of political awareness, distrust of the system, and limited administrative data. This study concluded that the KPU strategy was effective but still requires a more innovative and sustainable approach to optimize the political participation of novice voters in the future. Keywords: KPU Strategy, political partisipation, novice voters, regional head election, Jambi City